Estimating the depth and volume of surface runoff in the Wadi Al-Hussam Basin using the (SCS_CN) method (Soil Conservation Service) - Gharib, Dr. Duaa Mohammed (Thi Qar Arts Journal, 2024)
• The valley Hassam basin is one of the important valleys of the southern plateau in Iraq, which is located within the range of the lower valleys that end in the alluvial plain and flow into the Euphrates River. The crop receives annual rainfall and provides many groundwater reservoirs, which makes the economic value we invest in agricultural activity. Estimating the volume of surface runoff for this basin is very important for estimating the amount of surface water that can feed the basin, through the estimated surface runoff that later penetrates into the groundwater aquifers to feed the underground reservoirs, which are represented by the Euphrates, Dammam, and Lead formations. The mission of the study is to determine the depth of surface runoff for the Wadi Al-Hussam basin using the (SCS-CN) equation related to soil maintenance, as well as the volume of surface runoff for the basin. The valley Al-Hussam Basin is located in the southern Iraqi plateau within the Muthanna Governorate. The basin originates from the highlands of the southern plateau within the lower valleys’ region. It flows from the southwest to the northeast, as its sources end in the Sulaibat Depression. The length of the basin is (30 km). The basin consists of limestone rocks dating back to the Miocene period, dating back to the formation of the Euphrates and Dammam. The basin occupies a small area of ​​(158 km2) and is characterized by the presence of signs of exploiting its soil for agricultural production, as groundwater is available at depths ranging between 70-180 meters. It is also characterized by the presence of mixed soil suitable for agricultural production. The highest height in the basin was (120 meters) at the sources, while the lowest height was (20 meters) at the mouth. The depth of surface runoff in the case of wet soil reached (0.203), while the volume of surface runoff in plants reached ((0.032) million m3). In the case of High humidity and the volume of surface runoff in the basin was 15.65 mm), while the volume of surface runoff in the basin was (2.370 million m3).